Intellectual Emotion and Interactive Learning - Achilova Sohiba; Haydarova Namuna (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
The article highlights the pedagogical aspects of the correlation of intellectual emotions in the effective teaching of students and pupils through the use of interactive teaching methods